Design of Fuzzy Adaptive PID Temperature Controller Based on FPGA - Gang Qin; Yanni Ma; Xiangzhou Zhang; Ming Zhang (Institute of Advanced Engineering and Science, 2013)
Aiming at the characteristics of a certain thermostat control system such as non-linear and time varying, combining the traditional PID controller with modern fuzzy control theory, and using the EP1C12 FPGA as the core controller, the fuzzy adaptive PID temperature controller is going to be designed and achieved. The deviation and deviation rate are the inputs of fuzzy PID controller. PID parameters are the outputs of fuzzy PID controller. A set of fuzzy rules is used to achieve the online optimal regulation for the PID parameters. The simulation results of the system show that this method can significantly improve the control effect. With the simplification of the design, the computational speed and reliability of the system are also improved. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3459